2003
DOI: 10.1021/np030122f
|View full text |Cite
|
Sign up to set email alerts
|

An Anxiolytic-Like Effect ofGinkgo bilobaExtract and Its Constituent, Ginkgolide-A, in Mice

Abstract: The anxiolytic-like effects of Ginkgo biloba extract (GBE) and its four terpenoid components (ginkgolide-A, ginkgolide-B, ginkgolide-C, and bilobalide) were assessed using the elevated plus-maze test in mice. Administration of GBE as a single oral dose (0.5 or 1 g/kg, po) caused a state of suppressed motor activity and, thus, shortened the time spent in the open-sided arms. However, when GBE (0.063-1 g/kg, po) was administered daily for 7 days and the plus-maze test was carried out 24 h after the final adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…It is noteworthy that the highest doses tested here (25 mg/kg) significantly increased the time required to complete the maze, suggesting that some non-memorial effects may occur following high dose parenteral Ginkgo administration. Suppression of motor activity by a single oral dose of G. biloba extract (500 and 1,000 mg/kg but not 250 mg/kg) have also been reported elsewhere (Kuribara et al 2003).…”
Section: Discussionsupporting
confidence: 60%
“…It is noteworthy that the highest doses tested here (25 mg/kg) significantly increased the time required to complete the maze, suggesting that some non-memorial effects may occur following high dose parenteral Ginkgo administration. Suppression of motor activity by a single oral dose of G. biloba extract (500 and 1,000 mg/kg but not 250 mg/kg) have also been reported elsewhere (Kuribara et al 2003).…”
Section: Discussionsupporting
confidence: 60%
“…In anxiety rodent models, ginkgolides A, B, C, and bilobalide (individually and combined) were tested using the EPM paradigm with mice (Kuribara, Weintraub, Yoshihama, & Maruyama, ). The study found significant dose‐dependent relationships between ginkgolide A with reductions in anxiety (i.e., increased open arm time).…”
Section: Resultsmentioning
confidence: 99%
“…Several individual Chinese herbs not included in our top 10 commonly used regimens are still used for the treatment of insomnia in clinical practice. Some of these Chinese herbs have been reported to have anxiolytic-like effects, including Corydalis turtschaninovii (Yan-hu-suo) [43], Ginkgo biloba (Bai-guo) [44], Gardenia jasminoides (Zhi-zi) [45], and Gastrodia elata (Tian-ma) [46]. Others have been reported to have hypnotic effects, such as Stephania tetrandra (Fang-ji) [28].…”
Section: Discussionmentioning
confidence: 99%